Learning styles and critical thinking in accounting students at a public university in Cañete - Richard Chacaliaza, Carlos (2025)
The objective of this research is to establish the correlation between learning styles and critical thinking in accounting students from a public university in Cañete. The study group consisted of accounting students of both sexes from the public university of Cañete, totaling 120. Due to the large population, a census sampling was applied using the entire population as a sample. The study adopted a quantitative methodology in accordance with a basic level of non-experimental design. Likewise, it presented a descriptive-descriptive correlation level. The Sotelo Learning Styles Questionnaire (2022) and the Mesías Critical Thinking Questionnaire (2022) were the assessment instruments used. The findings indicate that there is a moderate negative correlation (-0.462) between the active style and critical thinking; However, the Reflective Style dimension shows a high positive correlation (0.763) with critical thinking, as does the Theoretical Style dimension, which shows a high positive correlation (0.763), all of which are relevant except for the correlation between the Pragmatic Style and Critical thinking, which shows a non-significant correlation. Thus, it can be deduced that there is a significant positive correlation (0.872) between learning styles and critical thinking.